2022
DOI: 10.1177/20501579221078674
|View full text |Cite
|
Sign up to set email alerts
|

Where horizontal and vertical surveillances meet: Sense-making of US COVID-19 contact-tracing apps during a health crisis

Abstract: Analyzing user reviews of seven US digital contact-tracing apps for COVID-19, this article unpacks how the new form of surveillance technology is understood and experienced by individuals during a global health crisis. The findings suggest that the app users felt empowered via self-tracking capacity and expressed community-level care and concerns, including those regarding the marginalized. At the same time, the users were raising doubts over technical effectiveness, navigating varying levels of voluntary choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The results found that despite shared concerns about privacy and surveillance issues, the Chinese people were more receptive to contact tracing applications than European and American people; for example, through the use of media and national discourse, China internalised its citizens’ use of the Health Code as a matter of national belonging (Kim et al, 2021; Zhang, 2021). In addition to people’s own willingness to use digital contact tracing applications, some scholars have suggested that national policy responses to these tools, such as mandatory or voluntary use, directly determine whether users adopt them to a greater extent (Baik & Jang, 2022). Typically, in countries or regions where the use of the application is voluntary, such as the United States, Germany, Singapore, and Australia, the use of the applications is limited (Goggin, 2020; Kostka & Habich-Sobiegalla, 2022), whereas, in places where the use is mandatory, guaranteed by public health laws, such as China and South Korea, the security incentives outweigh privacy concerns, prompting greater use of the tool.…”
Section: Health Code: Innovative Chinese Practice For Contact Tracing...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results found that despite shared concerns about privacy and surveillance issues, the Chinese people were more receptive to contact tracing applications than European and American people; for example, through the use of media and national discourse, China internalised its citizens’ use of the Health Code as a matter of national belonging (Kim et al, 2021; Zhang, 2021). In addition to people’s own willingness to use digital contact tracing applications, some scholars have suggested that national policy responses to these tools, such as mandatory or voluntary use, directly determine whether users adopt them to a greater extent (Baik & Jang, 2022). Typically, in countries or regions where the use of the application is voluntary, such as the United States, Germany, Singapore, and Australia, the use of the applications is limited (Goggin, 2020; Kostka & Habich-Sobiegalla, 2022), whereas, in places where the use is mandatory, guaranteed by public health laws, such as China and South Korea, the security incentives outweigh privacy concerns, prompting greater use of the tool.…”
Section: Health Code: Innovative Chinese Practice For Contact Tracing...mentioning
confidence: 99%
“…For users, in a complex social environment, privacy data is a source of contradiction and conflict in whether this application is used or not. Different attitudes towards privacy determine whether users use contact tracing applications when they have the choice (Baik & Jang, 2022), and the number of users in turn influences the accuracy of the tracing application (Kostka & Habich-Sobiegalla, 2022). Additionally, the long-existing class and digital gaps have raised concerns about the formation of a ‘second-order disaster’ caused by contact tracing applications (Madianou, 2020), and the degree of invisibility of other digital processing technologies, such as algorithms, reflects the ‘technological hegemony’ and ‘algorithmic hegemony’ of the critical school.…”
Section: Introductionmentioning
confidence: 99%
“…Such participatory surveillance as a tool to strengthen the sense of community can simultaneously lead to a sense of omnipresence of threat and reinforcement of fear (Mitchell, 2018; Purenne & Palierse, 2017). Ambivalence arises from the illusory sense of control and empowerment and the simultaneous fear associated with new surveillance technologies (Baik & Jang, 2022). At the same time, the category of “luxury surveillance” proposed by Chris Gilliard (2022) describes practices associated with the use of expensive electronic equipment, enabling the inclusion of more aspects of everyday life in the discourse of smart living, such as fitness apps.…”
Section: Appified Culture the “Soft” Digital Divide And Surveillancementioning
confidence: 99%
“…[17], [19], [20], [26], [41], [52], [53], [67], [68], [76], [94], [96], [99], [104], [109], [121], [123], [127] These articles take into account the quality attributes of functionality and security since they emphasize that all software must do the job for which it was developed and, nowadays, all software must have a decent degree of security since the Covid-19 pandemic has increased the rate of cybercrime. [18], [21], [22], [50], [54], [70], [125], [126] These articles take into account the quality attributes of functionality, performance, and reliability, they mention these quality attributes because they consider that software must perform its functions correctly with speed and accuracy, being able to operate with a large amount of data, such as the data generated by the Covid-19 pandemic, without having a long waiting time.…”
Section: Quality Attributes Artíclesmentioning
confidence: 99%